Modeling Health-Related Quality of Life: Insights from Higher Education Students in Kelantan / Mohd Azry Abdul Malik ... [et al.] - Abdul Malik, Mohd Azry; Fauzi, Aniq Ridhwan; Mohd Suzuki, Norazlina; Jaffar, Norazalina; Norzaki, Nur Ayuni; Romzai, Intan Suzieyana; Sahroni, Mohamad Norzamani; Ghazali, Jasrul Nizam; Kairan, Omar (Unit Penerbitan UiTM Kelantan, 2024)
Prioritising the quality of life among students is essential, as it directly impacts their academic performance, mental health, and overall well-being, laying the foundation for lifelong success and fulfilment. This study aims to determine the relationships between physical activity, sleep quality, lifestyle, and quality of life among university students. Another objective is examining potential differences in life quality according to gender. The study employed stratified random sampling to choose 80 participants from a prominent higher education institution in Kelantan. Data was gathered via self-administered questionnaires. Multiple linear regressions and the independent t-test were used in data analysis. Significant relationships between lifestyle and quality of life are shown by the study’s findings. The findings also revealed that physical activity and sleep quality did not significantly influence quality of life. Notably, no discernible differences in quality of life levels were observed between male and female students. The study provides valuable insights for higher education administrators and policymakers to enhance positive health-related quality of life among students.